Sacred and profane kriya in the island of Bali - I Ketut Sunarya; Ismadi (Cogent Social Sciences, 2024)
This article examines Balinese kriya’s development from sacred to profane. This research is qualitative research with a historical approach. The results show that the presence of past works cannot be separated from the purpose of the religious offering or ceremony. The kriya prehistoric period, which continued in the 8th to 10th centuries with the arrival of Hinduism, was a period of enlightenment. The sacred statues were born as symbols of gods, the island of Bali was a living museum of Javanese Hindu-Buddhism. The 10th to 13th centuries were the centuries of local Balinese genius, marked by kriya statues with a Balinese or folk character. The statue’s innocent character, short stature, and clothing match the character of the Balinese people at that time. In the 13th to 15th centuries, the baroque movement emerged. The presence of this movement is free, wild, and cheerful characters. In 1908, the Balinese kriya appeared passionate about imitating European styles. Openly, kriya began to fulfil needs outside of religion. The tourism development in Bali has brought about both kitsch and kriya retro. Kitsch is made for mass consumption, while kriya retro imitates great art. The desire to present the lost and destroyed past to preserve evidence in the form of replicas, copies, or imitations. It is hoped that the viewer will connect with that time or the social context of the era or place where the objects originated.